An Analysis of the Academic Information System Quality at Universitas Lancang Kuning (Smart Unilak) using the WebQual 4.0 and McCall Methods - Zarry, Cindy Kirana; Megawati, Megawati; Rahmawita, Medyantiwi; Salisah, Febi Nur (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
Websites have become an essential medium for information dissemination and marketing, particularly in the context of higher education. Universitas Lancang Kuning has implemented an Academic Information System (Smart Unilak) to improve the efficiency of academic services. However, observations and interviews with the PDDIKTI administrator revealed several issues, including a lack of updated information, difficulties in completing the Study Plan Card (KRS), and concerns regarding data security. To evaluate the system's quality, an analysis was conducted using the WebQual 4.0 and McCall methods. The WebQual analysis showed that the average respondent scores ranged from 3 to 4, which were interpreted as “Satisfactory” to “Very Satisfactory.” Additionally, the McCall method yielded an overall quality score of 89.28%, placing the system in the “Excellent” category. While respondents expressed satisfaction with the information and security provided by the system, there remains room for improvement in terms of communication ease. The findings of this study serve as an evaluation reference for website developers and a basis for future research. It is recommended that subsequent studies incorporate direct usability testing with users to identify issues that may not surface through surveys and questionnaires. Observing users as they interact with the system can provide valuable insights for further enhancement.